Logística brasileira: um estudo teórico do modal aquaviário (cabotagem) - SILVA, Kalina Santos da (2015)
To meet the complexities found in the transportation of different goods, logistics has a number of routes or modes which are the procedures for conducting the products according to the load characteristics and application. They are modal logistics, means of transport, road, air transportation, pipeline, rail and water transport (cabotage). This work studied the waterway mode (cabotage), a pre-defined period, featuring its importance within the Brazilian transportation logistics. Was presented the current structure of modal above, prospects, limitations, and investment incentives by the Federal Government as well as the main bottlenecks. Initiated by a brief history of coastal shipping, through characterization of modes that make up the fabric of Brazilian transport, being necessary to address the expansion policy of the ports to be closely linked to modal said. Research applied quantitative and literature was used, which showed, despite all invested in the sector, the freight transportation demands in Brazil are far from being met, greatly impacting the impetus for the full development of Brazil. It is essential for the effective use of coastal shipping that plans / programs of the Federal Government to run on schedule and suffer no interruption. For it is necessary to erase short-term bottlenecks, such as infrastructure of ports, excess manpower in port operations and facilities of access to ports, without which we will continue to watch the loss of competitiveness of Brazilian products , both domestic and external, resulting from the vaunted "Brazil Cost". In addition, it was found that coastal shipping requires integration with other modes and to the fullness of its efficiency and effectiveness, this will only occur through multimodality. Therefore, it recommends itself as a complement to this work a unique study to treat multimodality.